Prevalence of polymorphisms in the ANKK1, DRD2, DRD3 genes and metabolic syndrome in refractory schizophrenia - Jeizziani Aparecida Ferreira Pinto; Pedro Henrique Batista de Freitas; Fernanda Daniela Dorneles Nunes; Paulo Afonso Granjeiro; Luciana Lara dos Santos; Richardson Miranda Machado (Universidade de São Paulo, 2018)
ABSTRACT Objective: to estimate the prevalence of TaqIA, -141C and rs6280 polymorphisms of the ANKK1, DRD2 and DRD3 genes and evaluate their association with the occurrence of metabolic syndrome in patients with refractory schizophrenia. Method: cross-sectional study conducted in the Extended Western Region of Minas Gerais, with refractory schizophrenic patients using the antipsychotic clozapine. Sociodemographic, clinical, anthropometric, biochemical and genetic data were collected. Univariate analysis of the data was performed. Results: seventy-two patients participated in the study and the occurrence of Metabolic Syndrome was observed in 47.2% of them. There was no association between Metabolic Syndrome and the studied polymorphisms. There was a statistically significant difference in the low HDL parameter with homozygous genotype for the C allele of the -141C polymorphism of the DRD2 gene. Conclusion: a high prevalence of MS was evidenced. The -141C polymorphism was associated with low HDL. Genetic analysis and identification of metabolic alterations in this group of patients can guide drug treatment and provide a better quality of life.